Effect of the calcium silicate-based sealer removal protocols and time-point of acid etching on the dentin adhesive interface - Morais, Jéssika Mayhara Pereira [UNESP]; Victorino, Keli Regina [UNESP]; Escalante-Otárola, Wilfredo Gustavo [UNESP]; Jordão-Basso, Keren Cristina Fagundes [UNESP]; Palma-Dibb, Regina Guenka; Kuga, Milton Carlos [UNESP] (Wiley, 2018)
The aim of the study was to evaluate the effects when acid etching on the dentin surface was immediately performed (I) or 7 days (D) after calcium silicate-based sealer (MTA Fillapex) removal, using 95% ethanol (E) or xylol (X). First study, 60 bovine incisor dentin specimens were impregnated with sealer and divided into six groups (n = 10): (EI), E + I; (XI), X + I; (ED), E + D; (XD), X + D, (UN), untreated and (MR), mechanical removal of sealer. Scanning electron microscopy (SEM) images (500×) were obtained from each specimen and scores assessed the sealer residues persistence. Second study, 60 specimens were similarly treated; however, the specimens were restored with composite resin after the removal protocols. Hybrid layer formation was evaluated using confocal laser microscopy (1,024×). Third study, 60 specimens were similarly obtained and subjected to micro-shear test to evaluate the effects of removal protocols on the bond strength of etch-and- rinse adhesive system to dentin. XI showed the highest persistence of sealer residues (p <.05), similar to MR (p >.05). EI showed the greatest hybrid layer extension, except in relation to UN (p <.05). XI and MR presented the lowest bond strength adhesive system to dentin (p <.05). Acid etching immediately after calcium silicate-based endodontic sealer removal using xylol presented the highest residues persistence and negatively affected the adhesive interface between dentin and etch-and-rinse adhesive system.
Keywords: dentin; endodontics; image analysis; scanning electron microscopy